PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS VIII SMP - Islamiati, Nur; Abidin, Zainal (Media Pendidikan Matematika, 2016)
The problem in learning mathematics at SMPN 11 Mataram that the student motivation and student learning outcomes are low. Moreover, the teacher never using cooperative learning model type make a match (finding couple game). Therefore the purpose of this research is to know the effect of cooperative learning model type make a match toward student motivation and student outcomes at the eight grade of SMPN 11 Mataram in academic year 2016/2017. The kind of this reseach was a experimental research. Experiment design was used that is quasi experiment with posttest-only control design. The sample technique of this research was used purposive sampling where in class VIIID were got (31 Student) as experiment class and VIIIE (30 Student) as control class. Based on data analyzed was got mean score student motivation of experiment class with 61,03 with good category, while the control class was got mean score 57,07 with good enough category. And the data student result of experiment class was got mean score 81,71 with successful point 80,64%. Whereas control class was got mean score 73,56 with successful point 53,33%. And t test about student result was got thitung > ttabel or 3,08 > 2,01. Furthemore the result of this research can be concluded, there is effect of cooperative learning model type make a match toward student motivation and student learning outcomes at the eight grade of SMPN 11 Mataram in academic year 2016/2017.